2020
DOI: 10.26452/ijrps.v11ispl3.3460
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric dentists’ preference on usage of hand ϑiles or rotary ϑiles for pulpectomy of primary molars - A retrospective study

Abstract: Dental caries is the most prevalent chronic condition of the oral cavity. Excessive tooth decay can inflame pulp requiring pulpal intervention. One such endodontic procedure done to treat pulpitis is pulpectomy which is defined as complete removal of coronal and Radicular pulp. It can be done through hand or rotary filing techniques. A rotary filing system is better over hand filing that it gives more conical canal, reduces preparation time and thus enhances child cooperation. To analyse the preference of pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…It has been reported in a survey study of 100 dentists in India that half preferred rotary files [ 38 ], whereas in a study of 50 dentists, 62% preferred only using hand files [ 39 ]. According to a retrospective study examining pediatric dentists’ file preferences [ 40 ], 86% of pedodontists preferred rotary files when treating their patients. Similarly, in our study, in which the participants reported that rotary files were preferred the most (47%), 85% of them used only hand files during deciduous root canal treatment when they were trainee students, but today they predominantly use rotary or pediatric file sets, suggesting that physicians prefer more technological techniques thanks to the reduced risk of aspiration of the instruments and the shorter treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in a survey study of 100 dentists in India that half preferred rotary files [ 38 ], whereas in a study of 50 dentists, 62% preferred only using hand files [ 39 ]. According to a retrospective study examining pediatric dentists’ file preferences [ 40 ], 86% of pedodontists preferred rotary files when treating their patients. Similarly, in our study, in which the participants reported that rotary files were preferred the most (47%), 85% of them used only hand files during deciduous root canal treatment when they were trainee students, but today they predominantly use rotary or pediatric file sets, suggesting that physicians prefer more technological techniques thanks to the reduced risk of aspiration of the instruments and the shorter treatment period.…”
Section: Discussionmentioning
confidence: 99%